La determinación tributaria y su impacto en el derecho de reserva de información personal - César Vinicio, Pilamunga Paullán (2020)
At present, urban environments tend to register high temperatures that exceed the normal average, displacing the green areas by asphalt and concrete, whose thermal properties contribute to the formation of Urban Heat Islands (UHI). The UHI is indicative that temperatures within the city are higher compared to those recorded in the surrounding rural areas. This effect gives rise to what is known as urban microclimate that affects the thermal comfort of the population but it is known that such temperature variation can also affect the microstructure of concrete. In this investigation, the thermal capacity of such material at strategic points within the city was analyzed, and then compared with the ambient temperature, in order to determine how the formation of a microclimate is influenced by concrete. The results of this research indicate that in the city of Riobamba the UHI is formed because the ambient temperature exceeds the average temperature of the rural areas and should be taken into account when setting the concrete and taking samples for testing.